Sustainable Wood Nanotechnologies for Wood Composites Processed by In-Situ Polymerization - Montanari, Céline; Olsén, Peter; Berglund, Lars A. (Frontiers in Chemistry, 2021)
The development of large, multifunctional structures from sustainable wood nanomaterials is challenging. The need to improve mechanical performance, reduce moisture sensitivity, and add new functionalities, provides motivation for nanostructural tailoring. Although existing wood composites are commercially successful, materials development has not targeted nano-structural control of the wood cell wall, which could extend the property range. For sustainable development, non-toxic reactants, green chemistry and processing, lowered cumulative energy requirements, and lowered CO2-emissions are important targets. Here, modified wood substrates in the form of veneer are suggested as nanomaterial components for large, load-bearing structures. Examples include polymerization of bio-based monomers inside the cell wall, green chemistry wood modification, and addition of functional inorganic nanoparticles inside the cell wall. The perspective aims to describe bio-based polymers and green processing concepts for this purpose, along with wood nanoscience challenges.